Purposely profitable : embedding sustainability into the DNA of food processing and other businesses - Wills, Brett (Chichester, West Sussex, UK ; Hoboken, New Jersey : John Wiley & Sons, 2016)
Competing and winning in today's competitive marketplace requires a strategy that includes sustainability. Business leaders who embrace it and convey a strong sense of purpose behind their strategy are propelling their organizations into revenue-increasing, cost-reducing outcomes. Purposely Profitable: Embedding Sustainability into the DNA of Food Processing and other Businesses provides a proven, step-by-step methodology for integrating sustainability into the strategic plan to develop a strategy that is sustainable and aligned to a greater purpose. This book notably includes the following: -A primer on Sustainability that defines Sustainable Business and presents the Business Case for Sustainability -What is an organizational purpose and why is it so important in today's competitive marketplace -Step by step instructions, supported by a case study, for developing each component of the strategic plan (Purpose, Vision, Strategic Pillars, KPI's, Goals, Programs Action Plans, and Tactical Execution) -A suite of tools and resources to support the development and execution of the strategic plan Scientists and managers in the global food supply chain, sustainability professionals, researchers, students, regulators, executives and business owners will come to learn and understand a powerful system for developing a strategy that is sustainable in order to maximize organizational performance.
Finding purpose -- Creating a shared vision -- Getting focused ? Pillar development -- Financial objectives -- Measuring what matters ? KPI development -- Setting expectations -- Goal development -- Adding value ? Program development -- Getting tactical ? Strategy execution.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organizational effectiveness; Food industry and trade; Sustainability; Strategic planning; Food industry and trade; Organizational effectiveness; Strategic planning; Sustainability; TECHNOLOGY & ENGINEERING / Food Science; Electronic books